Perfil sanitário e qualidade de ovos de criações semiconfinadas nos municípios de Apodi e Mossoró/ Rio Grande do Norte - Silva, Nícolas Lima (Universidade Federal Rural do Semi-Árido, 2019)
The market for products from poultry industry has become promising, however, many producers still do not adopt the demanding standards regarding the quality of the products offered. The aim of this study was to evaluate the health profile and the physical quality of semi-finned eggs produced in semi-confined municipalities of Apodi and Mossoró, State of Rio Grande do Norte. For the evaluation of the microbiological quality, 108 eggs of one day of laying were used, being analyzed for counting of total and thermotolerant coliforms, mesophilic counting, quantification of Staphylococcus aureus and Salmonella spp. In the parasitological analyzes, fresh excreta were collected directly from the floor, using the spontaneous sedimentation technique by the Hoffmann method and the Faust flotation method. To determine the internal and external quality, 135 fresh eggs were analyzed for absolute weight (g), relative weight of components (yolk, albumen and bark), height and width of egg, yolk and albumen, specific gravity (at 9 different concentrations of saline, yolk color, shell thickness), pH, Haugh unit calculation, albumen index and yolk index. According to the results of the microbiological analyzes were negative for total coliforms, thermotolerant, mesophilic and Salmonella spp in 100% of the samples. For quantification of Staphylococcus aureus, the results presented values lower than 1 x 103. Parasitological analyzes were significantly higher for Eimeria and Heterakis when compared to rainfall indexes, where the months with the highest relative humidity index and lower temperatures showed prevalence of ascarids. As for the quality characteristics, the eggs presented good pigmentation of the yolk and good internal and external quality. Thus, hygienic-sanitary management of poultry farms can be improved in order to reduce the occurrence of parasites and, however, the eggs produced have good physical and microbiological quality, therefore feasible to commercialization.
Monografia
Keywords: Avicultura alternativa; Parasitologia aviária; Produção animal; Sanidade avícola; Poultry alternative; Avian parasitology; Animal production; Poultry health; CIENCIAS AGRARIAS::ZOOTECNIA